RELEVANCE OF RELIGIOUS COURT DECISIONS REGARDING DISPENSATION IN CHILD MARRIAGE - Rifki Fakihudin; Pramestya Raharjanti; Muhammad Wahyu Saiful Huda (Indonesia Private Law Review, 2022)
Child marriage in Indonesia is very vulnerable and has been increasing in recent years. In fact, the granting of marriage dispensation in the Religious Courts triggers several legal consequences that arise. Whereas in practice the judge's consideration is not always accepted regarding the marriage dispensation, the judge can also decide to reject the application for child marriage by looking at the existing legal aspects. Based on these problems, the author explains two problems that are the focus of this paper, namely how the legal consequences of the marriage dispensation on child marriage and the relevance of Religious Court Decisions with positive law. This study used empirical juridical research methods. Using secondary data through literature studies such as laws and regulations, court rulings, and legal theory, the method of data analysis uses qualitative methods. Then, this research conducted an empirical study of the literature from online sources. With the receipt of the application for dispensation for marriage, the right to be able to carry out marriages will be obtained so that the marriages carried out are legally recognized by the state and religion. However, even if the judge rejects the application for dispensation for marriage, the applicant can file an appeal at the Supreme Court. In fact, the role of judges is very important and judges also need to be selective when issuing a request for a marriage dispensation so that the increase in child marriage in Indonesia can be prevented.